Nonseed plant Selaginella moellendorffii has both seed plant and microbial types of terpene synthases - Li, Guanglin (National Academy of Sciences, 2012)
Terpene synthases (TPSs) are pivotal enzymes for the biosynthesis of terpenoids, the largest class of secondary metabolites made by plants and other organisms. To understand the basis of the vast diversification of these enzymes in plants, we investigated Selaginella moellendorffii, a nonseed vascular plant. The genome of this species was found to contain two distinct types of TPS genes. The first type of genes, which was designated as S. moellendorffii TPS genes (SmTPSs), consists of 18 members. SmTPSs share common ancestry with typical seed plant TPSs. Selected members of the SmTPSs were shown to encode diterpene synthases. The second type of genes, designated as S. moellendorffii microbial TPS-like genes (SmMTPSLs), consists of 48 members. Phylogenetic analysis showed that SmMTPSLs are more closely related to microbial TPSs than other plant TPSs. Selected SmMTPSLs were determined to function as monoterpene and sesquiterpene synthases. Most of the products formed were typical monoterpenes and sesquiterpenes that have been previously shown to be synthesized by classical plant TPS enzymes. Some in vitro products of the characterized SmMTPSLs were detected in the headspace of S. moellendorffii plants treated with the fungal elicitor alamethicin, showing that they are also formed in the intact plant. The presence of two distinct types of TPSs in the genome of S. moellendorffii raises the possibility that the TPSs in other plant species may also have more than one evolutionary origin.